Inquiry Learning Methods to Increase Student Motivation and Learning Outcomes - Sundari, Sri; Utami, Seftiani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: The current learning process has changed from teacher-centred learning (TCL) to student-centred learning (SCL). Therefore, innovative learning models are needed to improve student learning outcomes and motivation. This study aimed to measure the effect of inquiry learning methods on student motivation and learning outcomes.Methods: This was a quasi-experimental approach with a pre-test and post-test control group approach. The samples were divided into 29 students as the intervention group and 29 students as the control group. The researcher used the MSLQ (Motivated Strategies for Learning Questionnaire) to measure learning motivation. Meanwhile, to assess student learning outcomes, researchers used an assessment using the MCQ (multiple-choice question) learning outcomes evaluation method. The study's results were analysed using the paired sample t-test with a value of 0.05.Results: The study results in the intervention group showed the average value of the pretest learning motivation was 135.33, and the posttest-3 was 158.03, while the pretest-3 was68.43 and the posttest-3 was 83.03. The results of the different tests for learning motivation were obtained by pre-posttest-1 p-value of 0.012, pre-posttest-2 p-value of 0.000, pre-posttest-3 p-value of 0.001, while the study results from pre-posttest-1 to pre-posttest-3 obtained p-value = 0.000.Conclusion: There is an influence of inquiry learning method on the motivation and learning outcomes of Nursing Students.